Kajian Analisis Perhitungan Sistem Penggerak Katrol Listrik di PT. Jasa Marina Indah - Hariningrum, Rita; Utomo, Sukarno Budi (Marine Science and Technology Journal, 2022)
The development of increasingly advanced technology requires the industrial world to carry out the production process quickly and easily by prioritizing quality and quantity. One of the tools that can help the production process (transportation equipment) is a pulley that serves as a means of support to speed up the production process or move goods from one place to another. Main parts of electric pulley include Hoist, Pulley, Trolly. This study describes the design of an electric pulley system that is capable of lifting a load of 2000 kg. With a lifting speed of Hoist 20 m/s, Pulley 10 m/s, Trolly 5 m/s. The results show that the electric pulley drive system design with the above specifications produces a motor power of 61.393 kw Hoist, 30.6971 kw Pulley, 15.3482 kw Trolly.